PENYELESAIAN SENGKETA EKONOMI SYARIAH DI PENGADILAN AGAMA BEKASI - Azma, Ummi (Nurani, 2017)
In interacting with each other in community life often leads to conflict. This conflict can sometimes be resolved peacefully, but occasionally the conflict creates ongoing tension that causes losses on both sides. In order to defend the rights of each party it does not exceed the limits of the prescribed norm, the act of its own accord should be avoided. If the parties feel that their rights are disrupted and incur losses, then the person who feels his right is disadvantaged can file a lawsuit to the Religious Courts in accordance with the applicable procedures. This article is a summary of research results on the settlement of the Sharia economic dispute in the Religious Court of Bekasi.